Individual differences in the way observers perceive humour styles - Robyn Brown; Bruce Malcolm Findlay; Jay Brinker (The European Journal of Humour Research, 2019)
Humour has been conceptualized as styles, which vary based on their function (Martin, Puhlik-Doris, Larsen, Gray, and Weir, 2003). Research examining if and how observers perceive this intent is limited. The current study addresses this research gap by examining the perceptions of Martin et al.’s (2003) four humour styles. Additionally and of particular interest, was whether self-defeating humour and another self-directed humour style, self-deprecating humour, were perceived as two independent humour styles. Despite being similar in content, self-deprecating humour is associated with higher self-esteem and self-defeating humour with lower self-esteem.  Two hundred and four students watched comedy clips and completed a survey online. Participants were asked to categorize each video clip by humour style and to rate the self-esteem of the target (i.e. comedian). Results revealed that humour styles are distinguishable by observers with participants predominantly selecting one humour style over the others for each clip.  In support of the second hypothesis, targets who were categorised as using self-deprecating humour were perceived as having higher self-esteem than those categorised as using self-defeating humour, illustrating a distinction in the perception of these humour styles at an interpersonal level.